It Takes Partners to Create Solutions Management Wants. (November 2019) - Banks, Cristina G.; Mosier, Kathleen L.; Kennedy, Kriss J.; Miller, Christopher; Imada, Andrew S.
The notion of interdisciplinarity is inherent in the principles of human factors and ergonomics. HFE can be described as a multi-disciplinary, user-centric 'bundling science, ' in that it applies theory, principles, and data from many relevant disciplines to the design of work systems, taking into account the complex interactions between the human and other humans, the external environment, tools and equipment, and technology to enhance human performance and well-being (Wilson, 2000). The 2017 HFES Annual Conference panel addressed how to increase management's perceived value of HFE by changing the focus of HFE from risk to enhanced employee wellbeing, performance and productivity. This panel furthers this discussion by addressing how HFE can increase its perceived value by partnering with other disciplines to solve a critical organizational problem. We use the example of the Mars spacecraft habitat design to illustrate how HFE and other disciplines can intersect to create a living, working and recreational space that supports astronaut health, wellbeing and performance. First, Mosier describes HFE's increasing role in interdisciplinarity. Mosier also discusses habitat design from the perspective of team and psycho-social factors. Kennedy describes how architectural and engineering factors affect astronauts' physiological and psychological well-being. Miller discusses the role automation and technology will play in habitat functioning to keep astronauts safe and healthy. Banks adds concepts of psychological need satisfaction through habitat design to maintain astronaut health and well-being. Imada closes the panel with the role of HFE in the design of suitable human interfaces and consideration of how all elements function together as an effective system. The audience will be invited to contribute their own ideas for how these different disciplines can work together with HFE to create a healthy and productive habitat.